Perancangan WebGIS Penyebaran Lapangan Olahraga Bulutangkis di Kota Samarinda Menggunakan Quantum GIS dengan Plugin NextGIS Connect - Purba, Mentari Maruba Nasib; Suryalfihra, Shabri Indra; Sutaji, Ahmad Aris Mundir; Itsnani SM, A. Arifin (Journal of Geomatics Engineering, Technology, and Science, 2025)
This research is motivated by the increasing interest of the people of Samarinda City in badminton. The growing enthusiasm has led to a rising demand for accessible and accurate information regarding badminton court rentals. With numerous courts available, there is a need for an information system that can help the public find and choose courts that best suit their needs and preferences. The aim of this study is to design and develop a WebGIS (Web-based Geographic Information System) that maps the distribution of paid badminton courts in Samarinda City. This WebGIS provides not only spatial information but also detailed attribute data, including court names, addresses, available facilities, opening hours, rental prices, and visual documentation in the form of interior photos and exterior videos of the buildings. This system is intended to assist users in easily accessing information and receiving recommendations for suitable courts. The method used in this study is the Geographic Information System (GIS) approach, which functions to manage, analyze, and present both spatial and non-spatial data. Data processing is conducted using QGIS software, and the WebGIS is published using the NextGIS Connect plugin for online display. The result of this research is an interactive WebGIS that presents the distribution of 44 paid badminton courts across Samarinda City. Each location point is equipped with detailed information, including the name, address, facilities, coordinates, operating hours, rental prices, contact details, photos, and video documentation of the location. The distribution of courts includes: 8 courts in Sungai Pinang District, 7 in Samarinda Ulu, 6 in Loa Janan Ilir, 5 in Samarinda Utara, 5 in Samarinda Kota, 5 in Sambutan, 4 in Sungai Kunjang, 2 in Samarinda Seberang, and 1 court each in Palaran and Samarinda Ilir Districts